Correction to: Advances in the automated synthesis of 6-[18F]Fluoro-L-DOPA - Ângela C. B. Neves; Ivanna Hrynchak; Inês Fonseca; Vítor H. P. Alves; Mariette M. Pereira; Amílcar Falcão; Antero J. Abrunhosa (SpringerOpen, 2021)
An amendment to this paper has been published and can be accessed via the original article.